Analysis Product Quality and Price on Purchase Decision of Drinking Water in Packaging Aqla - Andi Dewi Aulia Mallombasang; Reni Furwanti; Adrianus Aprilius (STIE Amkop Makassar, 2020)
The bottled drinking water industry is growing due to the increasing level of community needs. So the company must make a marketing strategy in order to survive and win competitors. The population in this study were 464 consumers majoring in musamus university management and determining the sample using the Slovin formula was a sample of 61 people. data collection using a questionnaire. The method used is multiple linear analysis method. Test results prove that product quality and price have a positive influence on purchasing decisions. This should be a concern for management CV Tirta Alam Jaya Merauke will be quality products and prices because it affects the purchasing decision.